Ugaritic Textbook. Grammar. Texts in Transliteration. Cuneiform Selections. Glossary. Indices - Gordon, Cyrus H. (1965)
Völlige Neubearbeitung von 17:a:24 unter Einschluss der in PRUV veröffentlichten Texte.